A mathematical programming framework for early stage design of wastewater treatment plants. (February 2015) - Bozkurt, Hande; Quaglia, Alberto; Gernaey, Krist V.; Sin, Gürkan
Abstract: The increasing number of alternative wastewater treatment technologies and stricter effluent requirements make the optimal treatment process selection for wastewater treatment plant design a complicated problem. This task, defined as wastewater treatment process synthesis, is currently based on expert decisions and previous experiences. This paper proposes a new approach based on mathematical programming to manage the complexity of the problem. The approach generates/identifies novel and optimal wastewater treatment process selection, and the interconnection between unit operations to create a process flow diagram. Towards this end, a superstructure approach is used to represent the treatment alternatives for reaction and separation. A generic process interval model is used to describe each alternative in terms of input–output mass balances including conversion and separation factors. Next the design problem is formulated as a Mixed Integer (Non)linear Programming problem – MI(N)LP – and solved. A case study is formulated and solved to highlight the application of the framework. Highlights: A mathematical programming based approach for municipal WWTP design is proposed. A superstructure based optimization framework is developed for WWT process selection. A generic process interval model was developed to represent the treatment alternatives. The application of the framework was tested on a carbon/nitrogen removal case study. The case study problem was solved for several economic objective functions.